1998
DOI: 10.2134/jeq1998.00472425002700040010x
|View full text |Cite
|
Sign up to set email alerts
|

Plant Biomass and Elemental Changes in Shrubland Forages following Biosolids Application

Abstract: Land application of biosolids is a viable management practice for agriculture, but minimal information exists on beneficial uses for native rangeland. This study was conducted to determine the effect of surface-applied biosolids on the canopy cover, aboveground biomass, and nutrient status of native plant species in a sagebrush (Artemisia spp.) community in western Colorado. Biosolids were applied once in 1991 at nine rates consisting of 0, 5, 10, 15, 20, 25, 30, 35, and 40 Mg ha -t to plots measuring 3320 m s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 0 publications
6
45
0
1
Order By: Relevance
“…These findings are similar to those obtained by Biondini and Redente (1986), who reported that plant diversity decreases in the presence of high nutrient levels. No similar pattern was found by Pierce et al (1998), who reported that perennial grasses and shrubs remain the dominant species in a semiarid shrubland after biosolid treatment.…”
Section: Discussionmentioning
confidence: 48%
“…These findings are similar to those obtained by Biondini and Redente (1986), who reported that plant diversity decreases in the presence of high nutrient levels. No similar pattern was found by Pierce et al (1998), who reported that perennial grasses and shrubs remain the dominant species in a semiarid shrubland after biosolid treatment.…”
Section: Discussionmentioning
confidence: 48%
“…For good plant establishment, however, the physicochemical and biological properties of soil usually need to be improved. (Garcı´a et al, 1994;White et al, 1997;Pierce et al, 1998). To achieve this, urban organic wastes such as biosolids or municipal solid wastes might be employed-a useful alternative to simply disposing of them.…”
Section: Introductionmentioning
confidence: 99%
“…According to Sommers (1977), anaerobically produced biosolids from a variety of sources had a mean organic-C content of 27?6% and a mean total-N concentration of 5%. Relatively few studies have been conducted to document the effects of land application of biosolids on semi-arid rangelands (Fresquez et al, 1990;Benton & Wester, 1998;Pierce et al, 1998;Jurado & Wester, 2001). Application of biosolids to semi-arid rangelands represents a sound manner of recycling biosolids because it helps to enhance soil nutrient levels in these $ environments (Fresquez et al, 1990).…”
Section: Introductionmentioning
confidence: 99%